Java and MongoDB rapid app prototyping developer talk - Gee, Trisha J.; Safari eBooks ([S.l.] : Addison-Wesley Professional, 2015)
"In this Developer Talk, Java engineer Trisha Gee demonstrates with live coding how to build a web application in one hour. On the front-end, she uses AngularJS, HTML5, JavaScript, and Bootstrap. On the back-end, Dropwizard, MongoDB, Morphia, Gradle, and Groovy are utilized, and Spock is used for testing. The coffee shop web application built in this video enables users to select their coffee, place the order, and pick it up at their nearest coffee shop."--Resource description page.
Title from title screen (viewed November 22, 2014).
Presenter, Trisha Gee.
Keywords: MongoDB; Java (Computer program language); Application software -- Development; Electronic books